The European Citizens' Initiative: An Assessment of European Citizenship as a Solution to the Democratic Deficit in the European Union - Bejstrup, Katharina (My University, 2014)
The European Union (EU) introduced the European Citizens’ Initiative (ECI) in the Lisbon Treaty as a means of strengthening citizen involvement in the European decision-making process. The ECI allows a minimum of one million EU citizens to request that the European Commission submit a legislative proposal on the issue of the initiative. The ECI is, however, not only a means of strengthening participatory democracy in the EU. It also bears the potential to democratise the EU by facilitating the emergence of a general European public sphere since it essentially encourages European citizens to debate issues of European relevance across national borders. This is relevant because it is often claimed that the EU suffers from a democratic deficit. The aim of this paper is to assess the potential of the ECI as a solution to the democratic deficit in the EU. For this purpose, both the normative concepts of the democratic public sphere and citizenship based on secondary literature and the empirical concept of European citizenship based on an analysis of the “sites” of European citizenship, i.e., EU Treaties, the Acquis communautaire and European citizenship practices, will be examined. According to normative theories, citizenship is both a constitutive element and a prerequisite for a democratic public sphere. Citizenship is composed of rights and duties, participation and identity. The paper proposes a normative theoretical model of democracy as a point of reference for the assessment of European citizenship as well as for the discussion of the ECI as a solution to the democratic deficit. Previous research evaluates the ECI based on its practical implications or its contribution to participatory democracy. Instead, this paper contextualises the ECI as part of the empirical concept of European citizenship. This is based on the assumption that the democratic deficit is actually a citizenship deficit. The assessment of European citizenship conducted in this paper finds that the ECI only has limited potential as a catalyst for the emergence of a European public sphere since European citizenship deviates significantly from normative standards. Furthermore, a democratisation of the EU will inevitably bring about the end of European nation-states. As a result, European citizens face a democratic dilemma.
Keywords: European citizenship; European Citizens’ Initiative; public sphere; democratic deficit; fi=Julkisjohtaminen|en=Public Management |; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|